Analisis Pengujian Dry Gas Seal Type 28AT Tandem untuk Meningkatkan Reliability Dry Gas Seal di Kompresor Setrifugal - Nuradi bin Raswin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
Dry gas seal testing is one of the stages in the repair and maintenance of dry gas seals because without testing dry gas seals will have fatal consequences, which can cause more severe damage to the compressor and repair of humans and the environment. In the operation and maintenance of centrifugal compressors, especially gas compressors, there is often damage to dry gas seals or even if they are not damaged dry gas seals must be kept in a health check so that they can be used optimally and their reliability can be improved. In conducting a health check or repairing dry gas seal, one of the determinants of success is through static and dynamic testing using the DGS test rig or the other. Therefore it is very important in testing this dry gas seal that the author tries to learn how to complete the tests that must be considered in the testing procedure. In this study it can be concluded that the maximum speed used reaches 11429 rpm, when compared to the procedure is 1 - 1,225 x rpm in the compressor then the rotation obtained according to the procedure is (1,225 x 10000 = 12250 rpm maximum), with conditions 11429 rpm already fulfilling standard and is still within tolerance of testing rounds.